Sumudu decomposition method for Solving fractional-order Logistic differential equation - Mtawa, Ahmad H; Mahdy, A. M. S; Mohamed, A. S (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In This paper, we propose a numerical algorithm for solving nonlinear fractional-order Logistic differential equation (FLDE) by using Sumudu decomposition method (SDM). This method is a combination of the Sumudu transform method and decomposition method. We have apply the concepts of fractional calculus to the well known population growth modle inchaotic dynamic. The fractional derivative is described in the Caputo sense. The numerical results shows that the approach is easy to implement and accurate when applied to various fractional differentional equations.